2000
DOI: 10.1016/s0272-6386(00)70009-6
|View full text |Cite
|
Sign up to set email alerts
|

Differences in quality of life across renal replacement therapies: A meta-analytic comparison

Abstract: o A meta-analysis compared emotional distress and psychological well-being across renal replacement therapies (RRTs) and examined whether differences could be explained by: (1) treatment modalities, (2) case mix, or (3) methodologic rigor, Standard meta-analytic procedures were used to evaluate published comparative studies, Successful renal transplantation was associated with: (1) lower distress (effect size, d = -0.43 SD) and greater welf-being (d = 0.62 SD) than incenter hemodialysis (CHD) and (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
206
2
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(233 citation statements)
references
References 28 publications
11
206
2
10
Order By: Relevance
“…Sleep disorders are also known to have a negative effect on individuals' QoL and their physical and emotional wellness. 5,6,31,32 Parker et al determined that 85% of hemodialysis patients have major sleep disorders affecting their QoL. 33 Novak et al also reported that sleep disorders signifi cantly disturb individuals' QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorders are also known to have a negative effect on individuals' QoL and their physical and emotional wellness. 5,6,31,32 Parker et al determined that 85% of hemodialysis patients have major sleep disorders affecting their QoL. 33 Novak et al also reported that sleep disorders signifi cantly disturb individuals' QoL.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 The better quality of life of transplant patients compared with hemodialyses patients, and the clinical improvement of some dangerous sleeprelated problems (eg, sleep apnea or RLS) may erroneously suggest that sleep problems vanish after a successful transplant. [26][27][28] An association between RLS and insomnia in patients on maintenance dialysis has been suggested already by papers. [29][30][31] In our study, RLS and sleep disturbances were correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Bir meta-analizde böbrek nakli hastalarında yaşam kalitesinin diyaliz hastalarına göre daha iyi olmaya eğilim gösterdiği rapor edilmiştir (6). Böbrek nakli bekleme listesinde olup, uzun süredir diyaliz tedavisi görenlerde stres ve anksiyetenin sık olduğu bildirilmiştir (7).…”
Section: Giriş Ve Amaçunclassified